The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.ijsu.2008.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open cholecystectomy in cirrhotic patients: A prospective randomized study

Abstract: LC in cirrhotics is still complicated and highly difficult which associates with significant morbidity compared with that of patients without cirrhosis. However, it offers lower morbidity, shorter operative time; early resume dieting with less need for blood transfusion and reducing hospital stay than OC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 23 publications
2
54
0
Order By: Relevance
“…CTP class was calculated using prothrombin time, albumin, bilirubin, and clinical findings of ascites and encephalopathy [18]. CTP score was stratified as class A (5-6), B (7-9), and C (10)(11)(12)(13)(14)(15). MELD score was calculated by using preoperative values of three laboratory tests: international normalized ratio (INR), serum total bilirubin (TBil), and serum creatinine (Cr).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CTP class was calculated using prothrombin time, albumin, bilirubin, and clinical findings of ascites and encephalopathy [18]. CTP score was stratified as class A (5-6), B (7-9), and C (10)(11)(12)(13)(14)(15). MELD score was calculated by using preoperative values of three laboratory tests: international normalized ratio (INR), serum total bilirubin (TBil), and serum creatinine (Cr).…”
Section: Methodsmentioning
confidence: 99%
“…prospective randomized trial comparing open cholecystectomy (OC) and LC has been published [11], but more studies are needed in order for solid conclusions to be made.…”
mentioning
confidence: 99%
“…Misidentification of biliary structures is the leading cause of biliary injury and patient related factors may contribute to this error. Although the latter point is controversial, these injuries are more often seen in difficult cases (40)(41)(42)(43)(44)(45)(46)(47)(48). Lack of experience is a risk factor, but injuries may also occur in the hands of experienced surgeons (49,50).…”
Section: Biliary Injury A) What Are the Risk Factors For Bile Duct Inmentioning
confidence: 99%
“…One study showed that open cholecystectomy for cirrhotic patients had an 11-fold risk of 30-day mortality compared to open cholecystectomy for noncirrhotic patients (13). Mortality after open cholecystectomy in cirrhotic patients varied between 0% and 7.7% (14,15). Most complications and deaths have been related to bleeding from the gallbladder bed , postoperative liver failure, and systemic infection.…”
Section: Discussionmentioning
confidence: 99%